2021
DOI: 10.15294/maj.v10i1.43916
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Justice and Organizational Citizenship Behavior: The Mediating Roles of Organizational Commitment and Leader Member Exchange

Abstract: This study aims to examine the effect of organizational justice on organizational citizenship behavior with organizational commitment and leader-member exchange as mediating variables for sewing employees of PT. Apparel One Indonesia 1. The sample used is 92 respondents with the sampling technique using purposive sampling. The data collection method used a questionnaire. Methods of data analysis using descriptive statistical tests with analysis tools, namely SmartPLS 3.0. The conclusion of this study is that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…It was determined that the perception of OJ has a positive effect on OC. Our research results support the research results in the literature (AlMazrouei & Zacca, 2021;Hasyim & Palupiningdyah, 2021;Jehanzeb & Mohanty, 2019;Novitasari et al, 2020). This result shows that the OC of employees can be increased if OJ is provided in businesses.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was determined that the perception of OJ has a positive effect on OC. Our research results support the research results in the literature (AlMazrouei & Zacca, 2021;Hasyim & Palupiningdyah, 2021;Jehanzeb & Mohanty, 2019;Novitasari et al, 2020). This result shows that the OC of employees can be increased if OJ is provided in businesses.…”
Section: Discussionsupporting
confidence: 90%
“…OJ is one of the key factors affecting the success of an organization (Tahseen & Akhtar, 2016). Studies show that employees exhibit positive behaviors and attitudes such as organizational citizenship (Hasyim & Palupiningdyah, 2021), work engagement (Özer et al, 2017), and job performance (AlMazrouei & Zacca, 2021) in situations where OJ is provided. Conversely, when the perception of organizational injustice occurs in the employees, they display negative behaviors and attitudes toward the organization, such as organizational cynicism (Sen et al, 2021) and turnover intention (Aryani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, fairness in the organization does not lead directly to OCB. Prior studies explored several intervening variables between OJ and OCB, such as organizational commitment ( Donglong et al., 2020 ; Jehanzeb and Mohanty, 2019 ), organizational trust ( Ullah et al., 2021 ), job satisfaction ( Junru and Huang, 2019 ; Khan et al., 2020 ), job involvement ( Sujono et al., 2020 ), psychological ownership ( Jnaneswar and Ranjit, 2021 ), and leader-member exchange ( Hasyim and Palupiningdyah, 2021 ; Sheeraz et al., 2020 ). However, there is still a call to uncover the “black box” remaining in the OJ—OCB relation ( Ambrose et al., 2021 ; Rana et al., 2018 ; Zayed et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aguiar-Quintana et al (2020) found that continuous organizational commitment significantly positively affects interpersonal relationships in OCB. Hasyim and Palupiningdyah (2021) also argue that organizational justice positively affects organizational commitment and further affects OCB. Therefore, this study concludes that job attitudes should also have a significant influence on service-oriented OCB, leading to the following hypothesis.…”
Section: Participatementioning
confidence: 99%